PENGARUH GAYA KEPEMIMPINAN, PENGEMBANGAN KARIR DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT.PERKASA INTERNUSA MANDIRI MEDAN - Sembiring, Fransiska; Sitanggang, Darna (Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine the effect of leadership style, career development and job satisfaction on employee performance at PT. Perkasa Internusa Mandiri Medan. Data was collected by distributing questionnaires to 67 respondents. From the results of the study obtained multiple regression equations as follows: Y = 2,919+ 0,322X1 + 0,396X2+ 0,445X3 + . All regression coefficients are positive, meaning that all independent variables, namely leadership style, career development and job satisfaction, have a positive effect on the dependent variable, namely employee performance. Of the three independent variables, job satisfaction has a greater influence on employee performance because it has the largest regression coefficient of 0.445. Based on partial hypothesis testing, leadership style, career development and job satisfaction have a significant effect on employee performance where the significance value of each variable is smaller than alpha (0.05). Based on simultaneous hypothesis testing, the three independent variables, namely leadership style, career development and job satisfaction have a significant effect on the dependent variable, namely employee performance. This can be seen from the significance value of 0.000 < alpha (0.05). The coefficient of determination (R Square) of 0.766 means that employee performance can be explained by leadership style, career development and job satisfaction of 76.6% while the remaining 23.4% is explained by other variables not explained in this study such as motivation, communication and competence. From the results of research and discussion, PT. Perkasa Internusa Mandiri Medan should develop and maintain indicators of leadership style, career development and job satisfaction on employee performance at PT. Perkasa Internusa Mandiri Medan.